Pengaruh Motivasi Orang Tua Terhadap Kepribadian Anak - nurhasan; Nopiyanti (Edusifa: Jurnal Pendidikan Islam, 2023)
This study aims to determine the effect of parental motivation on children's personality. This research was conducted at MTs Insan Asli Nanggewer, Cibinong, Bogor. By using quantitative methods . With a research sample of 30 students. Data collection techniques used are questionnaires, observation and documentation. The sampling method was carried out randomly, (random sampling) from 131 MTs Insan Sejati students. In this study the instrument used a total of 30 statement items, with a parent motivation questionnaire of 20 statement questions, and a child personality questionnaire of 10 statement questions. The analysis technique used is inferential statistics using the SPSS 25 program. The results show that there is a correlation between parents' motivation on personality and values correlation 0.992 X 100 = 99.2% with rate correlation perfect. It can be concluded that the higher the motivation, the higher the performance that is affected or the lower the motivation, the lower the performance influenced.